Enhancing the efficiency of academic transcript generation: A case study of iReport designer at Politeknik Seberang Perai - Mohamed Nasir, Nur Hazwani; Mohammad Othman , Mohd Shafirol; Bakhari, Noazri (Jurnal Penyelidikan Sains Sosial, 2025)
The increasing student enrolment at Politeknik Seberang Perai has intensified the need for an efficient, user-friendly, and cost-effective academic transcript generation system. To meet this demand, the Examination Unit has adopted iReport Designer, an open-source reporting tool that streamlines the process. With this tool, transcripts can be generated and printed instantly by entering a student’s registration number, eliminating the need to navigate complex system menus. Its intuitive editing interface also enables easy modifications without the manual steps required in the Polytechnic Management Information System (SPMP). The use of a two-column transcript template further enhances cost-efficiency by reducing paper usage. Moreover, the system allows access to historical student records stored in the PMIS database, even if they are no longer available in SPMP. iReport Designer supports multi-database integration and is accessible by all Examination Unit staff, ensuring operational continuity. Overall, the implementation of iReport Designer has significantly improved the efficiency, accessibility, and cost-effectiveness of academic transcript generation. This study underscores the value of open-source tools in enhancing administrative processes in educational institutions.